PENERAPAN DYNAMIC SOFTWARE GEOGEBRA DAN CABRI 3D DALAM PEMBELAJARAN MATEMATIKA - Rahadyan, Andri; Halimatussa'diah (Jurnal Pemikiran dan Penelitian Pendidikan Matematika (JP3M), 2019)
This study aims to elaborate on the dynamic software GeoGebra and Cabri 3D in mathematics learning. The research method used is library research. This study uses the documentation method for collecting the data. The data analysis technique is content analysis. The results of this research are the collaboration of GeoGebra and Cabri 3D dynamic software as dynamic software with various features that can be used in mathematics learning to explore, visualize, and construct mathematical concepts and can be a tool in improving the quality of learning. GeoGebra has more features than Cabri 3D as it can explore the concepts of algebra, 2D geometry, 3D geometry, calculus, matrices, vectors, and statistics. Cabri 3D can only be used to explore the concepts of 2D geometry and 3D geometry.